2004
DOI: 10.1093/oxrep/grh031
|View full text |Cite
|
Sign up to set email alerts
|

The European Bond Markets under EMU

Abstract: In this paper, we document how in the wake of monetary unification the markets for Euro-area sovereign and private-sector bonds have become increasingly integrated. Issuers and investors alike have come to regard the Euro-area bond market as a single one. Primary and secondary bond markets have become increasingly integrated on a pan-European scale. Issuance of corporate bonds has taken off on an unprecedented scale in continental Europe. In the process, both investors and issuers have reaped the considerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
138
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(152 citation statements)
references
References 11 publications
13
138
0
1
Order By: Relevance
“…Some of the research then focused on the analysis of the relative importance of systemic versus idiosyncratic risk factors in explaining yield spreads in Europe after the introduction of the common currency, even though the empirical evidence was not conclusive. Several studies [Geyer et al (2004) and Pagano and Von Thadden (2004), among others] stressed the importance of systemic risk in the behaviour of yield differentials in EMU countries, while others showed that the idiosyncratic risk component in the movements of spreads was greater than the systemic risk [e.g., Goméz-Puig (2009), Dötz and Fischer (2010) and Favero and Missale (2012)]. All in all, studies whose data end before the global financial crisis coincided in stating that euro area bond markets shared a high degree of financial integration (see, e.g., Abad et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the research then focused on the analysis of the relative importance of systemic versus idiosyncratic risk factors in explaining yield spreads in Europe after the introduction of the common currency, even though the empirical evidence was not conclusive. Several studies [Geyer et al (2004) and Pagano and Von Thadden (2004), among others] stressed the importance of systemic risk in the behaviour of yield differentials in EMU countries, while others showed that the idiosyncratic risk component in the movements of spreads was greater than the systemic risk [e.g., Goméz-Puig (2009), Dötz and Fischer (2010) and Favero and Missale (2012)]. All in all, studies whose data end before the global financial crisis coincided in stating that euro area bond markets shared a high degree of financial integration (see, e.g., Abad et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The Euro has profoundly transformed the European debt securities markets (Pagano and von Thadden, 2004;Galati and Tsatsaronis, 2003;Hartmann et al, 2003). Specifically, it eliminated the exchange rate risk for cross-border investment in debt securities as between issuers and investors from the EMU.…”
Section: Investorsmentioning
confidence: 99%
“…Pagano and von Thadden (2004) note that euro area sovereign and private bond markets have become more integrated in the wake of monetary unification. They notice that governments laid the institutional framework for an integrated market, but that integration was also significantly promoted by the response of financial intermediaries for example in the form of panEuropean trading platforms.…”
Section: Introductionmentioning
confidence: 99%
“…4 Indeed, recently one has observed a remarkable increase in spreads of EMU countries relative to Germany. 5 In fact, fundamental risk factors are found to matter in EMU (Beber, Brandt, and Kavajecz (forthcoming), Hallerberg and Wolff (2008)) as well as in Germany (Heppke-Falk and Wolff 2008) while the importance of liquidity factors has declined with EMU (Codogno, Favero, and Missale (2003), Pagano and von Thadden (2004), Gómez-Puig (2006)). However Favero, Pagano, and von Thadden (2008) demonstrate, that EMU bond yield spreads are affected by an aggregated risk factor and the interaction of this risk factor and liquidity differentials between the considered bonds.…”
Section: Introductionmentioning
confidence: 99%